SOLVABILITY OF BOUNDARY VALUE PROBLEMS WITH NON-LOCAL CONDITIONS FOR MULTIDIMENSIONAL HYPERBOLIC EQUATIONS - Koshanov, B.D.; Koshanova, G.D.; Azimkhan, G.E.; Segizbayeva, R.U. (Academic Scientific Journal of Computer Science, 2020)
In this paper, we study the solvability of new nonlocal boundary value problems for hyperbolic equations in a multidimensional bounded domain. For the problem under study, the existence and uniqueness theorems of regular solutions are proved.